Nanocarbon from pine wood sawdust and its biocomposites applications - Perry Law, Nyuk Khui; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Al-Khalid, Othman; Jamal, Uddin; Kuok, Kuok King (Elsevier Ltd., 2024)
The development and utilization of nanocarbon in innovative biocomposite products are receiving special attention from researchers. Most researchers' study covers the development of carbon based materials which range from activated carbon, carbon fiber, carbon nanotubes, nanocarbon powders, and graphene. However, the studies conducted on the source of the nanocarbon and utilization of the nanocarbon for further biocomposite development and applying to their respective applications are not a popular research topic. Therefore, in this book chapter, the topic regarding the development of nanocarbon from Pine wood sawdust biomass and the possible applications from the biocomposites developed are specifically selected. The compilation of studies compiled showcases the nanocarbon potential application in various fields, methods for developing nanocarbon from pine wood sawdust, characterization of the developed nanocarbon, and comparison with other types of nanocarbon. It also showcases the synthesis and characterization of properties of pine wood sawdust nanocarbon biocomposites, applications of the developed nanocarbon biocomposites, comparison over traditionally known composite materials, and future direction for improvements in this field of study.